TINGKAT KESEJAHTERAAN PETANI IKAN KERAPU CANTANG (Epinephelus sp) DI DESA LABUHAN KECAMATAN BRONDONG KABUPATEN LAMONGAN - Wachidatus Sa'adah; Khiqotul Milah (Universitas Galuh Ciamis, 2020)
Grouper fish is one of the leading commodities for export. With grouper cultivation, the income earned will be used to meet family needs, so that the level of family welfare increases. This research was conducted with the aim to find out the income and welfare level of the grouper cantang fish farmers. This research was conducted in Labuhan Village, Brondong District, Lamongan Regency. The method used is quantitative and qualitative methods. The results of the research stated that the income was profitable and the welfare level of the farmers was categorized as phase III plus welfare families.